Upaya Mengurangi Stunting Dengan Meningkatkan Ketahanan Pangan di Nias Selatan - Kristine Buulolo, Puput; Widian Saragih, Mujahid (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Food security is a condition where food is met for all people and countries at all times, reflected in food that is nutritious, safe, high quality, diverse, nutritious, affordable and does not conflict with the religion, beliefs and culture of the community. Food security is an important and strategic matter, because several countries have shown that no country can carry out development steadily until it is able to realize food security first. Law Number 18 of 2012 concerning Food ensures that the government together with the community achieves food security for all Indonesian people. Because Indonesia is a country with a large population and a high growth rate, efforts to achieve food security are a challenge that must be prioritized for the nation's welfare. Because there must be an institution that regulates availability, stability and consumption patterns. Indonesia is one of the countries that pays attention to the food of its people, through Presidential Decree No. 66 of 2021 the government established the National Food Agency. For this reason, the role of mothers throughout Indonesia is needed to intelligently and creatively increase family food security. Stunting is a condition where children are shorter than their age which is caused by a lack of physical energy for a long time. Malnutrition in babies can occur from in the womb until the baby is 2 years old. Only after the baby is 2 years old can he be seen